Concurrent sensitization to Aspergillus Fumigatus in tropical pulmonary eosinophilia - Sunil K. Chhabra; Devi Jyoti Dash (Monaldi Archives for Chest Disease, 2016)
Tropical pulmonary eosinophilia (TPE) is characterized by lung tissue and peripheral blood eosinophilia. Serum total IgE is also markedly increased in TPE. However, an association with asthma or other hypersensitivity conditions has not been described. During the diagnostic workup of three patients eventually confirmed to have TPE, hypersensitivity to the fungus, Aspergillus Fumigatus was found. However, there was no evidence of diseases of aspergillus hypersensitivity such as severe asthma with fungal sensitization (SAFS) and allergic bronchopulmonary aspergillosis (ABPA). This association however raises the possibility of a future risk of these potentially serious allergic respiratory manifestations.